Seasonal variation in leaf area index and its impact on the shading effects of vertical green facades in subtropical areas. (November 2022) - Zhang, Yu; Yang, Yuanqin; Zhang, Lei; Zhao, Cheng; Yan, Junru; Liu, Mingxin; Zhao, Lihua
Abstract: Vertical green facades (VGFs) are considered promising design strategies for reducing building energy consumption. The leaf area index (LAIv ) has been considered a critical parameter in evaluating the thermal behaviour of VGFs. The LAIv is not static for a plant and changes over seasons. However, research on the seasonal variation of the LAIv and its impact on the shading effects of VGFs is limited. The present study addresses this research gap. First, a shading coefficient (SC) model was developed to describe the capability of VGFs to intercept solar radiation. Then, the SC and one-year LAIv variations of two deciduous plants and one evergreen plant were observed to verify the accuracy of the SC model and develop the seasonal LAIv prediction (SLP) model. Finally, the SLP model combined with local climate parameters was employed to analyse the solar heat gain on the east, south, west, and north walls with and without VGFs. The results indicated that the VGFs composed of deciduous plants could be considered a self-adjusting shading system, intercepting over 90% of incident solar radiation in summer and transmitting approximately 75% of incident solar radiation in winter. Highlights: Proposed and verified a shading coefficient model of vertical green facades (VGFs). Recorded one-year leaf area index (LAIv ) variations of VGFs. Developed a seasonal LAIv prediction model. VGFs of deciduous plants can be considered a self-adjusting shading system.